Effect of Ge-doping on the short-wave, mid- and far-infrared intersubband transitions in GaN/AlGaN heterostructures. (26th October 2017) - Lim, Caroline B; Ajay, Akhil; Lähnemann, Jonas; Bougerol, Catherine; Monroy, Eva
Abstract: This paper assesses the effects of Ge-doping on the structural and optical (band-to-band and intersubband (ISB)) properties of GaN/AlGaN multi-quantum wells (QWs) designed to display ISB absorption in the short-wave, mid- and far-infrared ranges (SWIR, MIR, and FIR, respectively). The standard c -plane crystallographic orientation is considered for wells absorbing in the SWIR and MIR spectral regions, whereas the FIR structures are grown along the nonpolar m -axis. In all cases, we compare the characteristics of Ge-doped and Si-doped samples with the same design and various doping levels. The use of Ge appears to improve the mosaicity of the highly lattice-mismatched GaN/AlN heterostructures. However, when reducing the lattice mismatch, the mosaicity is rather determined by the substrate and does not show any dependence on the dopant nature or concentration. From the optical point of view, by increasing the dopant density, we observe a blueshift of the photoluminescence in polar samples due to the screening of the internal electric field by free carriers. In the ISB absorption, on the other hand, there is a systematic improvement of the linewidth when using Ge as a dopant for high doping levels, whatever the spectral region under consideration (i.e. different QW size, barrier composition and crystallographic orientation).